2022
DOI: 10.3390/app12041893
|View full text |Cite
|
Sign up to set email alerts
|

Cool Surface Strategies with an Emphasis on the Materials Dimension: A Review

Abstract: The need to tackle the urban heat island effect demands the implementation of cool surfaces as a mitigation strategy. This study comprehensively reviews the evolution of this research field from a materials perspective. It provides a bibliometric analysis of the relevant literature using the SciMAT software processing of bibliographic records from 1995 to 2020, for the evolution of cool surfaces. The results obtained show an increased interest in the field from 2011 to 2020, particularly for roof applications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Chaimae Mourou and others. (31) , this comprehensive study explores the evolution of cool surfaces as a mitigation strategy for urban heat island effects. It emphasizes the development of reflective materials and recommends eco-friendly and cost-effective solutions using recycled glass.…”
Section: Reviewing the Literature On The Role Of Technology In Enhanc...mentioning
confidence: 99%
“…Chaimae Mourou and others. (31) , this comprehensive study explores the evolution of cool surfaces as a mitigation strategy for urban heat island effects. It emphasizes the development of reflective materials and recommends eco-friendly and cost-effective solutions using recycled glass.…”
Section: Reviewing the Literature On The Role Of Technology In Enhanc...mentioning
confidence: 99%
“…Identically, the use of cool pigments allows for reducing the cooling energy consumption of residential buildings by 10 to 20% [35]. Experimental assessment by using infrared thermography allows us to conclude that the surface temperature of a facade coated with reflective paints of intense colors, with the incorporation of cool pigments, can decrease to 11 • C [36]. Moreover, it is reported that the application of cool pigments can reduce the energy consumption of buildings, mainly in tropical regions with strong sun radiation, emphasizing the use of specific pigments such as iron oxide (hematite) with titanium dioxide [37].…”
Section: Advancements In Enhancing the Performance Of Eticsmentioning
confidence: 99%
“…For example, innovative porous materials (PM) could be synthesized by bottom ash and silica fume (as raw materials) to promote a circular economy, and new solutions could be proposed to improve urban air quality, reducing PM concentrations [8]. Another example is the integration of glass in the fabrication of ceramic materials as fine particles with optimal dosage and particle size, in order to enhance their physical, mechanical, and thermal properties and improve the solar reflectance performance [9]. The design of ceramic tiles with recycled glass could contribute to the production of friendly construction materials to be applied in the design of cool surfaces [10], i.e., surfaces with reflective materials and coatings that reflect the solar energy radiation that hits building envelopes and urban areas [11], including roofs, facades, and pavements.…”
Section: Construction Phase Of Building: Using New Materials For Buil...mentioning
confidence: 99%